Effects of Low-Dose Recombinant Human Brain Natriuretic Peptide on Anterior Myocardial Infarction Complicated by Cardiogenic Shock - Pan,Yesheng (2017)
Abstract INTRODUCTION: The mortality due to cardiogenic shock complicating acute myocardial infarction (AMI) is high even in patients with early revascularization. Infusion of low dose recombinant human brain natriuretic peptide (rhBNP) at the time of AMI is well tolerated and could improve cardiac function. OBJECTIVE: The objective of this study was to evaluate the hemodynamic effects of rhBNP in AMI patients revascularized by emergency percutaneous coronary intervention (PCI) who developed cardiogenic shock. METHODS: A total of 48 patients with acute ST segment elevation myocardial infarction (STEMI) complicated by cardiogenic shock and whose hemodynamic status was improved following emergency PCI were enrolled. Patients were randomly assigned to rhBNP (n=25) and control (n=23) groups. In addition to standard therapy, study group individuals received rhBNP by continuous infusion at 0.005 µg kg−1 min−1 for 72 hours. RESULTS: Baseline characteristics, medications, and peak of cardiac troponin I (cTnI) were similar between both groups. rhBNP treatment resulted in consistently improved pulmonary capillary wedge pressure (PCWP) compared to the control group. Respectively, 7 and 9 patients died in experimental and control groups. No drug-related serious adverse events occurred in either group. CONCLUSION: When added to standard care in stable patients with cardiogenic shock complicating anterior STEMI, low dose rhBNP improves PCWP and is well tolerated.